Numerical methods of geomechanics tasks solution during coal deposits' development - Bondarenko, V.; Hardygora, M.; Symanovych, H.; Sotskov, V.; Snihur, V. (Розробка родовищ, 2016)
Purpose. Generalization of numerical modeling of geomechanical processes in the vicinity of mine workings by finite elements method and making recommendations for substantiation of suitable construction and behavior of rock massif physical model. Methods. Software packages SolidWorks Simulation (COSMOS/М) and ANSYS are used for geomechanical tasks solution. Findings. Solutions of geomechanical tasks dealing with topical issues of estimating stress-strain state of rock massif around underground workings of different functions are given. Data on the rock massif stress-strain state are received and recommendations on adequate and authentic reflection of its structural peculiarities (stratification and fracturing) are made. Physical model of rock condition (elastic, elastic-plastic, rheological diagrams and complete diagram of deformation taking into account weakening and fracturing) is presented. Originality. New data about the mechanism of movement processes of coal-bearing massif around mine workings considering stratification and cracks content, limit and out-of-limit deflection state in separate areas, and also the impact of rheological rock properties are received. Practical implications. Complex of geomechanical tasks solutions allow to increase credibility of rock pressure manifestations prediction and substantiate technical solutions for effective and safe operations at coal mines. Цель. Обобщение опыта численного моделирования методом конечных элементов геомеханических процессов вокруг горных выработок и формирование рекомендаций по обоснованию адекватного строения и поведения физической модели горного массива. Методика. Для решения задач геомеханики использованы пакеты прикладных программ SolidWorks Simulation (COSMOS/М) и ANSYS. Результаты. Приведены решения геомеханических задач по актуальным вопросам оценки НДС горного массива вокруг подземных выработок различного назначения. Получены закономерности поведения горного массива и даны рекомендации по адекватному и достоверному отражению его текстурных особенностей (слоистость и трещиноватость) и физической модели состояния горной породы (упругая, упругопластическая, реологическая, полная диаграмма деформирования с учетом разупрочнения и разрыхления). Научная новизна. Получен ряд новых закономерностей развития процессов сдвижения углевмещающего массива вокруг горных выработок с учетом его слоистости и трещиноватости, предельного и запредельного состояния в отдельных областях, а также влияния реологических свойств горных пород. Практическая значимость. Комплекс решений геомеханических задач позволяет повысить достоверность прогноза проявлений горного давления и обосновать технические решения по эффективному и безопасному ведению горных работ на угольных шахтах. Мета. Узагальнення досвіду чисельного моделювання методом скінченних елементів геомеханічних процесів навколо гірничих виробок і формування рекомендацій з обґрунтування адекватної будови й поведінки фізичної моделі гірського масиву. Методика. Для розв’язання задач геомеханіки використані пакети прикладних програм Solidworks Simulation (COSMOS/М) і ANSYS. Результати. Наведено розв’язання геомеханічних задач з актуальних питань оцінки НДС гірського масиву навколо підземних виробок різного призначення. Отримано закономірності поведінки гірського масиву й надано рекомендації з адекватного й достовірного відображення його текстурних особливостей (шаруватість і тріщинуватість) та фізичної моделі стану гірської породи (пружна, пружнопластична, реологічна, повна діаграма деформування з урахуванням знеміцнення і розпушення). Наукова новизна. Отримано низку нових закономірностей розвитку процесів зрушення вуглевміщуючого масиву навколо гірничих виробок з урахуванням його шаруватості й тріщинуватості, граничного й позамежного станів в окремих областях, а також впливу реологічних властивостей гірських порід. Практична значимість. Комплекс розв’язань геомеханічних задач дозволяє підвищити вірогідність прогнозу проявів гірського тиску й обґрунтувати технічні розв’язання з ефективного й безпечного ведення гірничих робіт на вугільних шахтах.